Distribute 2 to x and -2, and -6 to x and -2
2(x - 2) = 2x - 4
-6(x - 2) = -6x + 12
2x - 4 = 4x - 6x + 12
Simplify. Combine like terms
2x - 4 = (4x - 6x) + 12
2x - 4 = -2x + 12
Isolate the x. Add 4 to both sides, and 2x to both sides
2x (+2x) - 4 (+4) = -2x (+2x) + 12 (+4)
2x + 2x = 12 + 4
Simplify
4x = 16
Isolate the x. Divide 4 from both sides
4x/4 = 16/4
x = 16/4
x = 4
4 is your answer for x.
hope this helps
Answer:
37
Step-by-step explanation:
59 percent times 63 in total marbles is 37
Answer:
C=5
Step-by-step explanation:
3^ + 4^2 = 25
and the square root of 25 is 5 therefore C=5
Answer:
C
Step-by-step explanation:
< open circle, not ≤